2019
DOI: 10.1186/s12871-018-0673-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the sublingual microcirculation following aortic surgery under balanced or total intravenous anaesthesia: a prospective observational study

Abstract: BackgroundIn vascular surgery with aortic cross-clamping, ischemia/reperfusion injury induces systemic haemodynamic and microcirculatory disturbances. Different anaesthetic regimens may have a varying impact on tissue perfusion. The aim of this study was to explore changes in microvascular perfusion in patients undergoing elective open abdominal aortic aneurysm repair under balanced or total intravenous anaesthesia.MethodsProspective observational study. Patients undergoing elective open infrarenal abdominal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…However, propofol is structurally unrelated to other hypnotic compounds. It induces hypnosis rapidly and reliably, and has additive or synergistic hypnotic effects with many other agents (like barbiturates, benzodiazepines, opioids and ketamine) commonly used in anesthesia [ 88 ].…”
Section: Effects Of Different Anesthetics On Cortical Electrophysimentioning
confidence: 99%
“…However, propofol is structurally unrelated to other hypnotic compounds. It induces hypnosis rapidly and reliably, and has additive or synergistic hypnotic effects with many other agents (like barbiturates, benzodiazepines, opioids and ketamine) commonly used in anesthesia [ 88 ].…”
Section: Effects Of Different Anesthetics On Cortical Electrophysimentioning
confidence: 99%
“…We did not observe any differences regarding the outcomes of the study based on prior prostatectomy. However, we should be cautious about these results since the impact of general anaesthesia required for major surgery such as prostatectomy on cognitive impairment is controversial and complex [ 85 , 86 ]. Several studies have shown an association between exposure to surgery under general anaesthesia and the development of delayed neurocognitive recovery in only a subset of patients [ 85 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we should be cautious about these results since the impact of general anaesthesia required for major surgery such as prostatectomy on cognitive impairment is controversial and complex [ 85 , 86 ]. Several studies have shown an association between exposure to surgery under general anaesthesia and the development of delayed neurocognitive recovery in only a subset of patients [ 85 , 87 ]. There are conflicting data on the relationship between exposure to anaesthesia and the development of long-term neurocognitive disorders, or the development of dementia in the patient population with normal preoperative cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…From an anesthetic viewpoint, Kitajima et al reported the implementation of routine intravenous systemic heparinization following LUL after encountering a patient who developed cerebral infarction post-LUL. Along with this postoperative anticoagulant therapy, they changed the postoperative analgesia from epidural analgesia to intercostal nerve blocks with intravenous patient-controlled analgesia [ 13 ]. In this way, other methods of postoperative analgesia, such as continuous nerve blocks, may be utilized instead of epidural anesthesia if the risk factors for PV stump thrombus formation and prophylactic anticoagulation are established in the future.…”
Section: Discussionmentioning
confidence: 99%